2020
DOI: 10.1111/psyp.13527
|View full text |Cite
|
Sign up to set email alerts
|

Who are you talking to? The role of addressee identity in utterance comprehension

Abstract: Experimental evidence suggests that speaker and addressee quickly adapt to each other from the earliest moments of sentence processing, and that interlocutor‐related information is rapidly integrated with other sources of nonpragmatic information (e.g., semantic, morphosyntactic, etc.). These findings have been taken as support for one‐step models of sentence comprehension. The results from the present event‐related potential study challenge this theoretical framework providing a case where discourse level inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…We can also refer toLattner and Friederici (2003) andCaffarra et al (2020) as studies that observed P600 for semantic/pragmatic anomaly.Frontiers in Psychology | www.frontiersin.org…”
mentioning
confidence: 99%
“…We can also refer toLattner and Friederici (2003) andCaffarra et al (2020) as studies that observed P600 for semantic/pragmatic anomaly.Frontiers in Psychology | www.frontiersin.org…”
mentioning
confidence: 99%